Study on Dynamic Error Compensation of Laser Emitter for Digging Navigation System - Jingdao Fan (IEEE Photonics Journal)
Laser emitters are used to generate vertically intersecting structured light, which can provide a reference for pose measurement. Therefore, the accuracy of the pose measurement system is determined by the accuracy of laser emitter instruments. The motion joint errors of the mechanical structure of the laser emitter instrument are analyzed and the transverse and longitudinal error transmission models are established in this paper. On this basis, the dual-axis coupling model is established and the error simulation analysis is performed. A method of using spring traction for error compensation is proposed and compared with the error before compensation. The results show that the error is significantly reduced, and the average laser deflection angle is about 1/14 of the pre compensation value.